Prediction of ship icing in Arctic waters - Observations and modelling for application in operational weather forecasting - Samuelsen, Eirik Mikal (UiT Norges arktiske universitet, 2017)
The papers III and IV of this thesis are not available in Munin. Paper III: Samuelsen, E.M.: Ship-icing prediction methods applied in operational weather forecasting. (Manuscript). Published version in Quartelrly Journal of the Royal Meteorological Society, 144 (710), 13-33, is available at http://dx.doi.org/10.1002/qj.3174. Paper IV: Samuelsen, E.M. & Graversen, R.G.: Weather situation during observed ship-icing events off the coast of Northern Norway and the Svalbard archipelago. (Manuscript). Published version in Weather and Climate Extremes , is available at https://doi.org/10.1016/j.wace.2019.100200. A ship travelling in sub-freezing conditions may encounter sea spray, rain, fog or snow freezing onto various parts of it. Such ship icing is a well-known threat for those individuals who have served on ships operating in a cold marine climate. As de-icing techniques may be energy consuming, accurate prediction of icing is also desirable from a financial point of view. Throughout the last 60 years there have been several efforts trying to model this elusive phenomenon. However, the lack of accurate field observations poses questions to the accuracy of the state-of-the-art modelling approaches including the parameterization of the physical processes of the models. As a consequence, the current study presents and utilises icing data obtained from ship observations in Arctic-Norwegian waters supplemented with high-resolution reanalysis data. On the basis of a unique data set derived from observations recorded on a particular ship type of the Norwegian Coast Guard, a completely new icing model has been developed. Verification of this Marine Icing model for the Norwegian COast Guard (MINCOG) and comparison to currently-applied methods in operational weather forecasting, reveals higher accuracy of MINCOG compared to the other methods. Furthermore, the study stresses the importance of including wave information separately into marine-icing models rather than incorporating it in the wind-speed parameter. A major ...